Experimental and in-host evolution of triazole resistance in human pathogenic fungi - Handelman, Mariana; Osherov, Nir (Frontiers in Fungal Biology, 2022)
The leading fungal pathogens causing systemic infections in humans are Candida spp., Aspergillus fumigatus, and Cryptococcus neoformans. The major class of antifungals used to treat such infections are the triazoles, which target the cytochrome P450 lanosterol 14-α-demethylase, encoded by the ERG11 (yeasts) / cyp51A (molds) genes, catalyzing a key step in the ergosterol biosynthetic pathway. Triazole resistance in clinical fungi is a rising concern worldwide, causing increasing mortality in immunocompromised patients. This review describes the use of serial clinical isolates and in-vitro evolution toward understanding the mechanisms of triazole resistance. We outline, compare, and discuss how these approaches have helped identify the evolutionary pathways taken by pathogenic fungi to acquire triazole resistance. While they all share a core mechanism (mutation and overexpression of ERG11/ cyp51A and efflux transporters), their timing and mechanism differs: Candida and Cryptococcus spp. exhibit resistance-conferring aneuploidies and copy number variants not seen in A. fumigatus. Candida spp. have a proclivity to develop resistance by undergoing mutations in transcription factors (TAC1, MRR1, PDR5) that increase the expression of efflux transporters. A. fumigatus is especially prone to accumulate resistance mutations in cyp51A early during the evolution of resistance. Recently, examination of serial clinical isolates and experimental lab-evolved triazole-resistant strains using modern omics and gene editing tools has begun to realize the full potential of these approaches. As a result, triazole-resistance mechanisms can now be analyzed at increasingly finer resolutions. This newfound knowledge will be instrumental in formulating new molecular approaches to fight the rapidly emerging epidemic of antifungal resistant fungi.